Quantifying the synaptic vesicle‐associated protein, VAMP2, to verify changes in cerebrospinal fluid in preclinical stages of Alzheimer's disease: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Goossens, Julie; Dewit, Nele; Belbin, Olivia; Lleó, Alberto; Vanmechelen, Eugeen
Abstract: Background: Synapse loss, a pathological hallmark of Alzheimer's disease (AD), is quantified in the brain using synaptophysin in western blot and immunohistochemistry, while the in vivo imaging compound 11 C‐UCB‐J targets synaptic vesicle glycoprotein 2A (SV2A). Both proteins are characteristic of synaptic vesicles (SVs) and are found in the majority of synapses. Since synaptophysin is not stable in CSF or serum, it is not a suitable marker to monitor synaptic integrity in fluids (Schlaf et al ., 1998). Vesicle‐associated membrane protein 2 (VAMP2), another SV component critical for vesicular trafficking, was identified as potential fluid surrogate for synapse loss using relative quantification (Lleo et al ., 2019). Here, we have developed a new digital immunoassay for VAMP2 and evaluated its CSF profile in 226 samples from the AD continuum. For comparison the more established post‐synaptic marker Neurogranin (Ng) was included, which is expressed in dendrites of excitatory glutaminergic neurons. Method: The immunoassay (Simoa) for VAMP2 was established using a commercial rabbit mAb and a novel high‐affinity mouse mAb 15E4. CSF was measured in duplicate on the HD‐1 analyzer across cognitively normal controls (n=68), preclinical AD stage 1 (Amyloidosis +, n=31), preclinical AD stage 2 (Amyloidosis +, neurodegeneration +, n=8), prodromal AD (n=80) and AD dementia (n=39). Ng was quantified with ELISA (EUROIMMUN). Result: The assay was able to quantify VAMP2 in all CSF samples with an average CV below 10%. Three quality control samples had an inter‐/intra‐assay variability below 10%. VAMP2 levels correlated strongly with Ng in all AD stages (r=0.78‐0.96, p<0.0001). VAMP2 (p<0.0001) and Ng (p<0.0001) were decreased by 40% in preclinical AD stage 1. They were both elevated in the prodromal (VAMP2 25%, p=0.0009; Ng 70%, p<0.0001) and dementia group (VAMP2 25%, p=0.014; Ng 50%, p<0.0001). Conclusion: A novel immunoassay for VAMP2 is capable of detecting changes in different AD stages. CSF changes in VAMP2 and Ng precede clinical symptoms and CSF neurodegeneration markers in the AD continuum. In line with observations that CSF‐tau and CSF‐Aβ abnormality precede plaque and tangle load via PET imaging, future longitudinal studies relating synaptic fluid markers with synaptic PET ligands (i.e. 11 C‐UCB‐J) could extend these findings.